Numerical Heat Transfer and Fluid Flow 2022 (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Numerical Heat Transfer and Fluid Flow 2022" contains scientific articles on experiments and simulations of heat transfer in compressible and incompressible fluids, including single- and two-phase flows. The articles present the current state of knowledge, solve scientific and industrial problems, and set directions for future research. The Special Issue is addressed to specialists from around the world dealing with numerical modelling and experiments on heat transfer in flowing fluids.